Antiproliferative activity of withanolide derivatives from Jaborosa cabrerae and Jaborosa reflexa. Chemotaxonomic considerations - García, Manuela Emila (2012)
Three withanolides were isolated from the aerial parts of Jaborosa reflexa Phil. Jaborosa cabrerae Barboza yielded five sativolide withanolides (including jaborosalactones R, S, 38, and 39) and two trechonolide withanolides epimeric at C-23 (trechonolide A and jaborosalactone 32). In addition, five derivatives were obtained by chemical derivatization of jaborosalactone 38, and all compounds were fully characterized by 1D and 2D NMR spectroscopic studies. The in vitro antiproliferative activities of the major natural withanolides and the semisynthetic derivatives were examined against HBL-100, HeLa, SW1573, T-47D, and WiDr human solid tumor cancer cell lines. Some chemotaxonomic considerations are discussed.